Differences in Comorbidities and Clinical Burden of Severe Bronchopulmonary Dysplasia Based on Disease Severity - Kim, Hye-Rim; Jung, Young Hwa; Kim, Beyong Il; Kim, So Young; Choi, Chang Won (Frontiers in Pediatrics, 2021)
Background The present study compared baseline characteristics, comorbidities and clinical burden of preterm infants with type 1 and type 2 severe bronchopulmonary dysplasia (BPD) Collaborative classification. Methods This study was a prospective cohort study of preterm (<32 weeks) very-low-birth-weight infants. Severe BPD was divided into type 1 severe BPD requiring of ≥30% oxygen and/or noninvasive ventilation at 36 weeks postmenstrual age (PMA), and type 2 severe BPD requiring invasive mechanical ventilation at 36 weeks PMA. Baseline characteristics, comorbidities and clinical burden were compared between these two types of severe BPD. Results Of the 1,328 infants included, 983 (74.0%) developed type 1 severe BPD, and 345 (26.0%) developed type 2 severe BPD. Lower birth weight, small for gestational age, lesser maternal premature rupture of membrane, lower 5-min Apgar score, air leak, pulmonary hemorrhage, surgical ligation of patent ductus arteriosus, necrotizing enterocolitis, and late-onset sepsis were significantly associated with type 2 severe BPD. Compared with infants with type 1 severe BPD, infants with type 2 severe BPD had an increased risk of mortality (aOR 18.64, 95% CI 10.81-32.13), pulmonary hypertension (aOR 2.16, 95% CI 1.59-2.93), and tracheostomy (aOR 10.38, 95% CI 2.05-52.49). Conclusions Our data highlight the substantially greater mortality and clinical burden in infants with type 2 severe BPD than infants with type 1 severe BPD. A comprehensive and multidisciplinary approach is needed for infants with type 2 severe BPD.